2022
DOI: 10.1186/s12885-022-10079-4
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis of genomic and transcriptomic data reveals the prognostic relevance of human proteasome genes in different cancer types

Abstract: Background The human proteasome gene family (PSM) consists of 49 genes that play a crucial role in cancer proteostasis. However, little is known about the effect of PSM gene expression and genetic alterations on clinical outcome in different cancer forms. Methods Here, we performed a comprehensive pan-cancer analysis of genetic alterations in PSM genes and the subsequent prognostic value of PSM expression using data from The Cancer Genome Atlas (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Interestingly, knockdown of either DNMT resulted in the downregulation of specific core components of the proteasome machinery (Fig. 4G-H), which are also the targets of PIs (Larsson et al, 2022; Yadav et al, 2023), potentially reducing vulnerability to PIs. Above all, these data support the protective role of DNMT1 and DNMT3B downregulation against proteasome inhibition in CRC through modulation of the cellular transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, knockdown of either DNMT resulted in the downregulation of specific core components of the proteasome machinery (Fig. 4G-H), which are also the targets of PIs (Larsson et al, 2022; Yadav et al, 2023), potentially reducing vulnerability to PIs. Above all, these data support the protective role of DNMT1 and DNMT3B downregulation against proteasome inhibition in CRC through modulation of the cellular transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…In the past years, the correlation between elevated PSMA7 expression with adverse prognosis was reported by sporadic research 12 , 21 28 . Recently, a TCGA-based pan-cancer study mentioned briefly the prognostic valus of 49 proteasome family member genes including PSMA7 59 , which indeed serves as a significant precursor to our own research. During the explorations of CNA of chr20 using similar genomic data from TCGA tumors, we identified PSMA7 as the most potential target at the newly found amplicon of 20q13.33.…”
Section: Discussionmentioning
confidence: 99%
“…Then we at a pan-cancer level systematically explored the status of amplification and expression of the PSMA7 gene and their clinical significances in terms of prognosis and potential therapeutic opportunity. Distinguishing from the previous pan-cancer research focusing on the prognostic values of PSMA7 59 , we further investigated the underlying mechanism linking high PSMA7 expression to poor prognosis. Analysis of proteins interacting or genes correlating with PSMA7 revealed broad functions of PSMA7 in multiple cellular processes 13 , especially networks with proteasome binding or complex.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the proteasomal noncatalytic subunit PSMD2 interacted with MYH9 and induced its degradation via the ubiquitin-proteasome pathway in NPC. PSMD2, proteasome 26 S subunit ubiquitin receptor/ non-ATPase 2, is reported to be a key ubiquitin-proteasome-related gene for predicting prognosis in multiple cancer types [ 56 58 ]. PSMD2 physically interacts with p21 and p27 and mediates their degradation via the ubiquitin-proteasome pathway by cooperating with the deubiquitinating enzyme USP14, subsequently promoting cell proliferation and facilitating cell cycle progression in breast cancer [ 59 ].…”
Section: Discussionmentioning
confidence: 99%